Analysis of Resistance to Macrolide–Lincosamide–Streptogramin B Among -Positive Isolates - Mahmoud Khodabandeh; Mohsen Mohammadi; Mohammad Reza Abdolsalehi; Azadeh Alvandimanesh; Mehrdad Gholami; Meysam Hasannejad Bibalan; Abazar Pournajaf; Ramin Kafshgari; Ramazan Rajabnia (Osong Public Health and Research Perspectives, 2019)
Objectives Genetic determinants conferring resistance to macrolide, lincosamide, and streptogramin B (MLSB) via ribosomal modification such as, erm, msrA/B and ereA/B genes are distributed in bacteria. The main goals of this work were to evaluate the dissemination of MLSB resistance phenotypes and genotypes in methicillin-resistant Staphylococcus aureus (MRSA) isolates collected from clinical samples. Methods A total of 106 MRSA isolates were studied. Isolates were recovered from 3 hospitals in Tehran between May 2016 to July 2017. The prevalence of MLSB-resistant strains were determined by D-test, and then M-PCR was performed to identify genes encoding resistance to macrolides, lincosamides, and streptogramins in the tested isolates. Results The frequency of constitutive resistance MLSB, inducible resistance MLSB and MSB resistance were 56.2%, 22.9%, and 16.6%, respectively. Of 11 isolates with the inducible resistance MLSB phenotype, ermC, ermB, ermA and ereA were positive in 81.8%, 63.6%, 54.5% and 18.2% of these isolates, respectively. In isolates with the constitutive resistance MLSB phenotype, the prevalence of ermA, ermB, ermC, msrA, msrB, ereA and ereB were 25.9%, 18.5%, 44.4%, 0.0%, 0.0%, 11.1% and 0.0%, respectively. Conclusion Clindamycin is commonly administered in severe MRSA infections depending upon the antimicrobial susceptibility findings. This study showed that the D-test should be used as an obligatory method in routine disk diffusion assay to detect inducible clindamycin resistance in MRSA so that effective antibiotic treatment can be provided.